1998
DOI: 10.1074/jbc.273.3.1529
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of RGS4, a GTPase-activating Protein for G Protein α Subunits

Abstract: GTP hydrolysis by guanine nucleotide-binding proteins, an essential step in many biological processes, is stimulated by GTPase-activating proteins (GAPs). The mechanisms whereby GAPs stimulate GTP hydrolysis are unknown. We have used mutational, biochemical, and structural data to investigate how RGS4, a GAP for heterotrimeric G protein alpha subunits, stimulates GTP hydrolysis. Many of the residues of RGS4 that interact with Gi alpha 1 are important for GAP activity. Furthermore, optimal GAP activity appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 26 publications
6
119
0
Order By: Relevance
“…The GST construct alone had no effect ( Fig. 1 Aa); neither did boiled GST-RGS4 (n ϭ 4, not shown) nor did the mutant GST-RGS4 (N128H) (n ϭ 4, not shown), which lacks GTPaseactivating protein activity (13,21). Inhibition of K G channel activity by 1 M GST-RGS4 was essentially irreversible upon washout of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The GST construct alone had no effect ( Fig. 1 Aa); neither did boiled GST-RGS4 (n ϭ 4, not shown) nor did the mutant GST-RGS4 (N128H) (n ϭ 4, not shown), which lacks GTPaseactivating protein activity (13,21). Inhibition of K G channel activity by 1 M GST-RGS4 was essentially irreversible upon washout of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structure-function analysis of RGS proteins has revealed that the RGS homology domain or core domain is sufficient for GAP activity in vitro (12)(13)(14). In this study, we define a second functional domain of RGS4.…”
Section: Discussionmentioning
confidence: 99%
“…1A), is sufficient for the GAP activity of RGS4 in vitro (12)(13)(14). To define the minimal sequences required for RGS4 function in vivo, we used the ability of RGS4 protein to inhibit pheromone signaling in the budding yeast S. cerevisiae as an assay (11).…”
Section: Plasma Membrane Localization Of Rgs4 Is Required For Its Funmentioning
confidence: 99%
See 2 more Smart Citations